2012
DOI: 10.1007/s13197-012-0782-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in color-related compounds in tomato fruit exocarp and mesocarp during ripening using HPLC-APcI+-mass Spectrometry

Abstract: Tomato is an important agricultural crop worldwide. Their pigments are very important in many ways. They have been associated with health benefits such as lowering the risk of some chronic diseases. Quantification of chlorophylls by spectrophotometry and Identification of carotenoids using liquid chromatography coupled to mass spectrometry, and quantification by HPLC-DAD was carried out in the exocarp and mesocarp of tomato fruit during 6 different ripeness stages (mature-green, breakers, turning, pink, light-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 19 publications
5
15
0
Order By: Relevance
“…Last but not least, the pattern of changes observed for quality parameters agreed with previous reports [ 9 , 32 , 33 ]. Colour parameters related with ripening, such as the increase in a * and decrease in Hue angle, changed in a similar way as described by other authors [ 9 , 32 ] and paralleled the changes found in carotenoids. The sharp increase in red colour pigments, such as carotenoids, were reported between stages 2 and 5 of ripening (breaker to light red), together with a decrease in the L * value [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Last but not least, the pattern of changes observed for quality parameters agreed with previous reports [ 9 , 32 , 33 ]. Colour parameters related with ripening, such as the increase in a * and decrease in Hue angle, changed in a similar way as described by other authors [ 9 , 32 ] and paralleled the changes found in carotenoids. The sharp increase in red colour pigments, such as carotenoids, were reported between stages 2 and 5 of ripening (breaker to light red), together with a decrease in the L * value [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, analysis of the total color change parameter (ΔE*ab) depicted a highly significant difference (P < 0.05) between red (21.95–24.47) and yellow (7.72–26.26) or orange (3.13–7.59) flesh types as noted for a* or b* color components (Table 2). During the ripening stages of tomato fruit, both the meso and exocarp fruit tissues exhibited both decreased L* and b* values, and increased a* values in the fully ripened red color fruits [46]. This suggests that the observed color space characteristics of inbred watermelon lines with red flesh color are consistent with those in reported studies.…”
Section: Resultssupporting
confidence: 75%
“…According to the literature, changes in the skin color of tomatoes can be observed, changing from green (negative values of a*) to red (positive values of a*), in which the fruit ripens. This ripening process can occur due to the degradation of chlorophyll and lycopene synthesis in exocarp pigments 48,49 . The ethylene oxidation can be seen in the literature regarding quality postharvest maintenance and shelf‐life extension of the climacteric fruit and vegetables.…”
Section: Resultsmentioning
confidence: 99%